2020
DOI: 10.1503/cmaj.200642
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of convalescent plasma for severe COVID-19 based on evidence in other severe respiratory viral infections: a systematic review and meta-analysis

Abstract: Coronavirus disease 2019 (COVID-19) has been diagnosed in nearly 3 million individuals around the globe, of whom around 0.2 million have died. 1 Many patients with COVID-19 develop severe acute respiratory illness requiring admission to intensive care units (ICU) and often mechanical ventilation. 2 The case fatality rate in COVID-19 may be as high as 2.3% overall 2 and from 10% to 40% among severely affected individ uals. 3,4 There is an urgent need for effective therapies.Emerging epidemiologic and clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 34 publications
7
75
0
8
Order By: Relevance
“…However, the plasma therapy has been not yet approved for use by United States Food and Drug Administration, and numerous clinical trials are working on it (14). In our study, the administration of convalescent plasma did not improve the clinical status of the patient, similar to the study of Niveditha that has demonstrated that convalescent plasma has few or no clinical bene t for the treatment of COVID-19 (15). Karuna and colleagues have proven that the presence of bilateral pleural effusion among patients infected with MERS indicates a poor prognosis such as death.…”
Section: Discussionsupporting
confidence: 76%
“…However, the plasma therapy has been not yet approved for use by United States Food and Drug Administration, and numerous clinical trials are working on it (14). In our study, the administration of convalescent plasma did not improve the clinical status of the patient, similar to the study of Niveditha that has demonstrated that convalescent plasma has few or no clinical bene t for the treatment of COVID-19 (15). Karuna and colleagues have proven that the presence of bilateral pleural effusion among patients infected with MERS indicates a poor prognosis such as death.…”
Section: Discussionsupporting
confidence: 76%
“…[3][4][5] A recent systematic review on the use of CP in non-COVID-19 severe respiratory viral infections found no mortality benefit. 6 There is evidence that CP collected from COVID-19 survivors contains Receptor Binding Domain specific antibodies with potent antiviral activity. 7 However, effective titres of NAb, optimal timing for CP therapy, optimal timing for plasma donation, and the severity class of patients who are likely to benefit from CP therapy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Early during the outbreak, the usefulness of convalescent plasma transfusion was considered for treatment of severe cases 4 . Several large clinical trials have now been initiated to evaluate the efficacy and safety of convalescent plasma treatment of SARS-CoV-2 patients 5 .…”
Section: Introductionmentioning
confidence: 99%